Pengaruh Produk, Kualitas Pelayanan, dan Harga Terhadap Kepuasan Pelanggan Pada PT. Rajawali Nusindo di Banjarmasin - Kadir, Abdul; Jayen, Fredy; Amrulloh, Rifqi; Ningsih, Tira Wahyu (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2023)
This study aims to examine the effect of product, service quality and price on customer satisfaction at PT. Rajawali Nusindo in Banjarmasin. The research approach used is a quantitative approach. This type of research is causal associative, namely research that explains the influence of product variables, service quality and price on customer satisfaction at PT. Rajawali Nusindo in Banjarmasin. The population in this study was 2903 who were customers of PT. Rajawali Nusindo Banjarmasin. The sampling technique used is non-probability sampling using the accidental sampling method. The total sample is 97 people calculated using the Slovin formula. Data were analyzed using Instrument Test, Classical Assumption Test, and Multiple Linear Regression. The results of this study indicate that the variable product, service quality and price simultaneously have a significant effect on customer satisfaction at PT. Rajawali Nusindo Banjarmasin. The product variable has no partial significant effect on customer satisfaction, the service quality variable has a partial significant effect on customer satisfaction and the price variable has a partial significant effect on customer satisfaction. The price variable is a variable that has a dominant influence on customer satisfaction at PT. Rajawali Nusindo Banjarmasin.